APLIKASI DESKTOP PASIEN RAWAT JALAN PADA KLINIK MEKAR SARI MEDIKA MENGGUNAKAN METODOLOGI BERORIENTASI OBYEK - Padeli Padeli; Syarah Syarah; Rahmat Hidayat (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2015)
Pursue the world of business in the health sector needs support right information to manage health care services for the purpose of a health service can be implemented as expected. The dependence in the business world of computer-based information systems is rapidly increasing, making it difficult for a business organization to compete without the support of information systems that address the needs mempu. In thismatter as a desktop application into an ease of software in any application of computerized technology, as well as software (software). A desktop application that is designed to be answering the needs of users, who apply into the computerized system. So from that point on in the wake of an application can improve the system must be ensured before. Thus, as stated above, the Blooms Sari Medical Clinic is an organization that is engaged in work to improve health care quality and patient information needed in order to be accepted quickly and precisely so that the quality of service standards can be satisfied. To achieve these objectives, Sari Medical Clinic blooms are still using manual system of recording data in particular, causing health care to the patient to be slow. To answer this, we need a system of outpatient health services to support the smooth. The key to successful implementation of an outpatient information system is to understand the needs of the administration of the Medical Clinic and Sari Bloom understands the development of strategies that can facilitate the adoption and use of a new technology.